Development of physical ergonomics design guidelines for processing equipment in Malaysian offshore oil and gas platform / Mohd Hafizul Hilmi Mohd Noor - Mohd Hafizul Hilmi, Mohd Noor (2019)
The oil and gas industry in Malaysia contributes a significant portion of the local gross domestic product (GDP). The development of offshore oil and gas technologies and facilities design, in particular on operation and maintenance are critical issues during engineering design stages to ensure its efficiency and reliability. Since human physical intervention is inevitable in performing operation and maintenance tasks, physical ergonomics issues (PEI) are very crucial to be managed and mitigated through a careful consideration at early stages of the design process. This study aims to improve the implementation of physical ergonomics requirements during the early design stages of offshore processing equipment development. This is carried out through three objectives, which are to evaluate the effects of operator’s concerns and operational tasks towards the physical ergonomics requirements in an offshore processing equipment design, develop physical ergonomics design guidelines (PEDG) for mitigating the PEI during the early design stages, and validate the proposed PEDG. The study was conducted in three phases. Firstly, the respondents among local oil and gas practitioners with random backgrounds were required to evaluate three sections of a questionnaire survey: the relevancy of design criteria in an offshore workplace with the physical ergonomics domain, effects of physical ergonomics implementation in design, and criticality of PEI in an offshore workplace. Secondly, operational tasks for the maintenance of offshore processing equipment were classified based on three selected case studies: Fuel Gas Package, Air Dryer Package, and Nitrogen Generation Package. Hierarchical Task Analysis (HTA) was utilized to explore the physical tasks involved during maintenance activities. As a result, four common maintenance components were established: filtering, heating, membrane, and vessel iv components. Thirdly, all the physical tasks were assessed against the 15 predetermined PEI through a face-to-face interview session with five industry experts, then the consequences of the PEI towards an operator were evaluated. Ergonomics principles of workplace design—body dimension and body posture, muscular strength, and body movement—were applied to recommend the mitigation plans that could be applied as a basis for ergonomics design guidelines for the common maintenance components. The results showed that the operator’s concerns contributed towards the criticality rating of the PEI, which simultaneously had justified the proposed PEDG. Meanwhile, the assessment results on the operational tasks had influenced the ergonomic design requirement within a processing equipment through nine design themes: access space and reaching area, bolting, tripping and slipping hazards, materials handling, personal protection, valves and controls configuration, working at height, confined space, and others. In conclusion, this study had provided a significant understanding on the perception of stakeholders with respect to the physical ergonomics issues within a processing equipment, coupled with the combination of operational design requirements factors in developing the PEDG. This combination was found to be the best approach in ensuring the effective implementation of physical ergonomics during the early design stage of offshore processing equipment, consequently reducing the potential ergonomics risks within the facilities design.